Single Excited Dual Band Luminescent Hybrid Carbon Dots-Terbium Chelate Nanothermometer - Rustem R. Zairov (MDPI AG, 2021)
The report introduces hybrid polyelectrolyte-stabilized colloids combining blue and green-emitting building blocks, which are citrate carbon dots (CDs) and [TbL]+ chelate complexes with 1,3-diketonate derivatives of calix[4]arene. The joint incorporation of green and blue-emitting blocks into the polysodium polystyrenesulfonate (PSS) aggregates is carried out through the solvent-exchange synthetic technique. The coordinative binding between Tb3+ centers and CD surface groups in initial DMF solutions both facilitates joint incorporation of [TbL]+ complexes and the CDs into the PSS-based nanobeads and affects fluorescence properties of [TbL]+ complexes and CDs, as well as their ability for temperature sensing. The variation of the synthetic conditions is represented herein as a tool for tuning the fluorescent response of the blue and green-emitting blocks upon heating and cooling. The revealed regularities enable developing either dual-band luminescent colloids for monitoring temperature changes within 25–50 °C through double color emission or transforming the colloids into ratiometric temperature sensors via simple concentration variation of [TbL]+ and CDs in the initial DMF solution. Novel hybrid carbon dots-terbium chelate PSS-based nanoplatform opens an avenue for a new generation of sensitive and customizable single excited dual-band nanothermometers.